Alcor: Death Care Through Cryonics (Service After Death)!. Issue 1 (June 2022) - Ahmed, Jashim Uddin; Zabir, Faseeha; Islam, Quazi Tafsirul; Asif Gazi, Mohammad; Ahmad, Asma
After-death care service industry usually includes services of rituals that are associated with death, such as funerals, burials, and death memorials. Funeral homes and cemeteries are the most common types of business segments in this industry. Amidst the standard segments, a unique kind of segment is growing, and that is cryonics or cryopreservation. Alcor has been the market leader in the segment of cryopreservation because of their experience and unique services. The case aims to analyze the services and operations of Alcor. The analysis shows how Alcor achieves its success in the market with the help of its available resources.